(3CSGdjH JOQjHjI aj af GdedGceI hJYdje HQeLI GdegGQGJ s - (3ehSi LhGO(B, (3cGXes ((3GdbGgQI (B:s (3eQcR GdcJGH ddfTQ(B,s, 2023)
(3jYO gPG GdcJGH eQLYG ddHOA ai JYdje hJMSjf egGQGJ af GdedGceI GP jJfGhd CSGdjH JOQjHjI ai af GdedGceI hJYdje HQeLI GdegGQGJ hjJfGhd GdcJGH ehGVjY egeI LOG ai gPG GdPi jbjO GdeNJUjf hGdeOQHjf hGdOGQSjf dQjGVI GdedGceIs
(3GdeQGLY U(B.417s
Keywords: (3GdQjGVI GdHOfjI(B- (3GdedGceI s; (3GdedGceI (B- (3GdJOQjH s